In children with tmj dysfunction assessment of some indicators of oral fluid - Saidov A. A; Muminov D. B (International Journal on Human-Computing Studies, 2021)
The problem of the relationship between dental and somatic health in children and adolescents is of interest to researchers and does not lose relevance. First, this is due to the tendency to increase the frequency of somatic and dental diseases in children. Secondly, this is due to the fact that there are modern concepts of the development of diseases, new clinical forms of pathologies, improved methods of research, diagnosis and treatment (1,2,4,13).